Mutations observed in mitochondrial DNA of salmon collected in Mano River, Fukushima Prefecture, Japan - Fitri, Muhammad; Kawada, Gyo; Enomoto, Masahiro; Tomiya, Atsushi; Watanabe, Masato; Morishita, Daigo; Izumi, Shigehiko; Nakajima, Masamichi (Springer, 2020)
On March 11, 2011, a great earthquake occurred off the east coast of Honshu Island, Japan. The consequent breakdown of the Fukushima Daiichi Nuclear Power Plant (FDNPP) caused a massive release of radionuclides into terrestrial and marine environments and into the atmosphere. The Abukuma Mountains region is one of the areas highly polluted by this accident. Freshwater fishes continued to live in this area after the FNPP accident became so polluted.